International peritoneal dialysis training practices and the risk of peritonitis. Issue 5 (11th October 2021) - Cheetham, Melissa S; Zhao, Junhui; McCullough, Keith; Fuller, Douglas S; Cho, Yeoungjee; Krishnasamy, Rathika; Boudville, Neil; Figueiredo, Ana E; Ito, Yasuhiko; Kanjanabuch, Talerngsak; Perl, Jeffrey; Piraino, Beth M; et al.
ABSTRACT: Background: The effects of training practices on outcomes of patients receiving peritoneal dialysis (PD) are poorly understood and there is a lack of evidence informing best training practices. This prospective cohort study aims to describe and compare international PD training practices and their association with peritonitis. Methods: Adult patients on PD <3 months participating in the Peritoneal Dialysis Outcomes and Practice Patterns Study (PDOPPS) were included. Training characteristics (including duration, location, nurse affiliation, modality, training of family members, use of individual/group training and use of written/oral competency assessments) were reported at patient and facility levels. The hazard ratio (HR) for time to first peritonitis was estimated using Cox models, adjusted for selected patient and facility case-mix variables. Results: A total of 1376 PD patients from 120 facilities across seven countries were included. Training was most commonly performed at the facility (81%) by facility-affiliated nurses (87%) in a 1:1 setting (79%). In the UK, being trained by both facility and third-party nurses was associated with a reduced peritonitis risk [adjusted HR 0.31 (95% confidence interval 0.15–0.62) versus facility nurses only]. However, this training practice was utilized in only 5 of 14 UK facilities. No other training characteristics were convincingly associated with peritonitis risk. Conclusions: There was no evidence to support that peritonitis risk was associated with when, where, how or how long PD patients are trained.